Discussion on the reliability of NFV - Xu YANG; Ziyu XIAO; Yongping SHAO; Xiaoming SONG (Dianxin kexue)
Through the reduction of the hardware reliability which was caused by the introduction of NFV,the reliability issue of introducing NFV into telecommunication network was introduced.Through the analysis of reliability and availability of NFV,the typical fault scenarios,fault detection mechanism and processes of NFV architecture,and the NFV’s unique cross-layer detection mechanism and deployment advice was proposed.Finally,the NFV reliability requirements and design recommendations were proposed.